Islam Moderat dan Islam Radikal dalam Perspektif Generasi Milenial Kota Surabaya - Abdul DJalal (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2020)
This paper examines the results of several previous studies that took formal education as an object of research with respondents from students and teachers in the Jakarta, Bandung and Yogyakarta regions, who agreed to a change in state ideology from Pancasila to the Islamic Khilafah and acts of violence in religion. As a test tool, the authors offer research objects to milenials in Surabaya with formal and non-formal educational backgrounds and social settings of various professional backgrounds, education, and ages between 17 and 30 years and with in-depth observation methods and interviews with FGD techniques (Focus Group Discussion) on 13 young people of the city of Surabaya on four regions in the city of Surabaya. The results of this study indicate; first, Milenial generation narratives about moderate Islam show religious experiences that are relaxed, light, peaceful, and flexible and radical Islam as Islamic behavior that cannot adapt to its environment. The source of the reference shifts from book literacy to digital literacy by utilizing social media content, Instagram, and Youtube. Third. the figure and inspiration also changed from the figure of the ulama to the figures who perform ‘hijrah’, both artists and young clerics, and entertaiment products that utilize digital media.